The Effect of Using Letter Card Media On The Language Ability (Literacy) Of Children Aged 4-5 Years At RA Tsamaniatun Hasanah Medan-Binjai KM.13.5 In Academic Year 2021/2022 - Untari, Ladipa; Ladipa Untari (International Journal of Applied and Advanced Multidisciplinary Research, 2023)
The research aims to explain the significant influence of letter card media on the language (literacy) abilities of children aged 4-5 years at RA Tsamaniatun Hasanah for the 2021/2022 academic year. The research design uses one group pretest-posttest from the pre-experimental design. The population in this study were all class A children aged 4-5 years at RA Tsamaniaun Hasanah with a total of 15 children. The results of the research showed a total score (pre-test) of 65 and a total score (post-test) of 159. A comparison between the scores (pre-test) and the scores (post-test) of the experimental group was then analyzed and the result was W count = 0, W table = 25 with comparison conditions if W count 0 < 25 W table then Ho is rejected and Ha is accepted. Thus, the letter card media influences language skills (literacy) in class A RA TSAMANIATUN HASANAH Sei Semayang Village.